Locally Lipschitz Composition Operators in Space of the Functions of Bounded κΦ-Variation - Odalis Mejía; Nelson José Merentes Díaz; Beata Rzepka (Journal of Function Spaces)
We give a necessary and sufficient condition on a function h:R→R under which the nonlinear composition operator H, associated with the function h, Hu(t)=h(u(t)), acts in the space κΦBV[a,b] and satisfies a local Lipschitz condition.